Treatment Options for Infantile Spasms Syndrome with SCN8A: A Case Report and Literature Review - Oikawa, Shizuka; Yamaguchi, Hiroshi; Hanafusa, Hiroaki; Ye, Ming Juan; Tokumoto, Shoichi; Tomioka, Kazumi; Nishiyama, Masahiro; Morisada, Naoya; Nozu, Kandai; Nagase, Hiroaki (Journal of Pediatric Epilepsy, 2024)
“Infantile spasms syndrome (IS),” previously known as “West syndrome (WS),” is characterized by epileptic spasms (ES), abnormal electroencephalography (EEG) patterns such as hypsarrhythmia, and developmental stagnation or regression in infancy. IS has various etiologies, including genetic abnormalities. SCN8A variants are associated with developmental and epileptic encephalopathy, characterized by developmental delay, seizures starting from infancy, and refractory epilepsy with multiple seizure types. However, previous studies have not focused on the treatment of IS caused by SCN8A variants. We report a case of a previously healthy boy who presented ES and developmental regression at 6 months of age. His EEG revealed hypsarrhythmia, leading to the diagnosis of IS. After admission, the patient was treated with hormonal therapy using intravenous methylprednisolone pulse therapy (MPT). ES and hypsarrhythmia on EEG disappeared in the early stages of MPT administration with no observed treatment complications. Furthermore, we observed no recurrence of EEG abnormalities or seizures at 17 months of age. Genetic testing revealed a novel de novo SCN8A variant (NM_001177984.2:c.2882T > G:p. M961R). The literature review confirmed that 13 patients, including our described patient, were reported to have ES owing to missense variants of SCN8A. While the previous articles do not mention intravenous MPT for ES with SCN8A, our case findings suggest that intravenous MPT therapy may be effective for short-term suppression of ES caused by the SCN8A variant in IS.
Keywords: developmental and epileptic encephalopathy; electroencephalography; hypsarrhythmia; methylprednisolone pulse therapy; West syndrome